NUSHUZ PERSPEKTIF LALEH BAKHTIAR DALAM CONCORDANCE OF THE SUBLIME QUR'AN: (Sebuah Pandangan Feminisme dalam Tafsir) - Zaenatul Hakamah (Institut Agama Islam Negeri (IAIN) Keiri, 2019)
This research discusses about nushuz of wife and the husbands right to threat the nushuz of his wife. This focuses on Laleh Bakhtiars Perspektif on violence against women in the Quran surah 4:34. The word wadhribuhunna in the surah does not only mean to hit but there are a lot of meanings of it, however, her interpretation of Qur'an got several critics. This surah can be interpreted upon the perspective on social and fenimism context in the relation between husband and wife in Indonesia and how its defferent in the Islamic Country. This is a literate study that will employ a library research methodology as well to examine and analyze the Islam position in general on the surah vis a vis women beating practises conducted by the husband based on the surah. This can be considered as a hard evidence of how the Quran should not be interpreted in a physical context alone but rather in contextual perspective.